The Role of Digital Applications in Enhancing Qur’an Memorization Learning - Ary Asyari; Tasman Hamami; Sukiman Sukiman (Al-Qalam Institute, 2025)
This study investigates the integration of digital applications in Tahfidzul Qur’an learning to examine both opportunities and challenges in their implementation. The main objective is to understand how technology affects the effectiveness of memorization, as well as the factors that support or hinder its use. A qualitative field research design was employed, involving observations of memorization practices, interviews with teachers, students, and administrators, and documentation of teaching materials. Findings reveal several challenges: limited technical skills among teachers, insufficient technological infrastructure, resistance to adopting digital tools, and a lack of curriculum-aligned digital resources. Despite these barriers, digital applications show strong potential to enhance students’ motivation, engagement, and retention in Qur’an memorization. The novelty of this research lies in its systematic analysis of how traditional memorization methods can be adapted within a digital framework, highlighting both pedagogical and managerial dimensions. The study recommends targeted teacher training, infrastructure development, and collaboration with educational technology developers to design suitable digital resources. These efforts are expected to strengthen the quality of Islamic education and ensure its relevance in the digital era.